Synthesis, physicochemical characterization and evaluation of efficacy and toxicity of liposomes encapsulated mefenamic acid - Jarrar, Qais Bashir Mahmoud (2018)
Mefenamic acid (MFA) is a member of non-steroidal anti-inflammatory drugs (NSAIDs) with anti-inflammatory, anti-nociceptive and febrifugal properties. The poor aqueous solubility of this drug constitutes a major challenge in developing stable and effective formulations for the children in the pharmaceutical market. In light of this, this study was conducted to enhance the solubility and the therapeutic index of MFA using liposomes encapsulation technology. Various formulations of MFAloaded liposomes including MFA-liposomes, MFA-Tween 80 liposomes and MFAsoduim diethyldithiocarbamate (DDC) liposomes were prepared using the proliposomes method and were subjected to various in-vitro characterizations. The in vivo toxicity and therapeutic efficacy of these liposomes was evaluated in experimental rats using the oral and intraperitoneal routes at selected doses (0, 20, 40 and 80 mg/kg). The animals were observed for toxicity signs and were used in a number of selected biochemical, histological and ultrastructural investigations. The anti-inflammatory, anti-nociceptive and febrifugal efficacies were determined using carrageenan-induced paw edema model, carrageenan-induced thermal hyperalgesia test, yeast-induced pyrexia test and lipopolysaccharides-induced systemic inflammation model. The finding of the present study demonstrated that MFA-loaded liposomes showed different physicochemical properties, storage stability and reproducibility. In particular, MFA-DDC liposomes were homogeneous (polydispersity index was around 0.2) vesicles with smaller particles size (ranging from 157.50 to 177.14 nm) and higher entrapment efficiency (up to 94.08 %) compared to other formulations used in the present study. Also, MFA-DDC liposomes were physically stable when stored at the room temperature (18-22 ͦ C) and refrigerator (2-8 ͦ C) for a period of at least 28 days. In addition, these liposomes were reproducible with a relatively low coefficient of variation (not more than 7.2 %) between different prepared batches at all tested parameters. The maximum tolerated dose of the intraperitoneally administered MFA-loaded liposomes was 20 mg MFA/kg, whereas for those oral administration was up to 80 mg MFA/kg. The repeated administration of MFA-DDC liposomes caused significant elevation of serum alanine aminotransferase and aspartate transaminase at high oral dose (80 mg MFA/kg). on the other hand, blood levels of total bilirubin, alkaline phosphatase, triglycerides, cholesterol, total proteins, glucose, uric acid, blood urea nitrogen and creatinine, and uric acid as well as urine physicochemical parameters were not statistically affected. In contrast to MFA-DDC liposomes, the repeated administration of free MFA and MFA-Tween 80 liposomes resulted in hepatorenal histological and ultra-structural alterations in dose-dependent manner. Administration of MFA-DDC liposomes caused significantly higher inhibition in paw edema, pain sensation and fever than those of free MFA and MFA-Tween 80 liposomes administration. Results obtained from lipopolysaccharides-induced systemic inflammation revealed that MFA-DDC liposomes exhibited a significantly stronger suppression of serum proinflammatory mediators (PGE2, NO, IL-1beta, IL-6 and L-selectin) than that of free MFA and MFATween 80 liposomes dosage (80 mg MFA/kg). The findings of the present study showed that MFA-DDC liposomes have higher entrapment efficiency, smaller particles size, more reproducible and stable during storage than those of MFA liposomes and MFA-Tween 80 liposomes. MFA-DDC liposomes are also much safer and more suitable than MFA-Tween 80 liposomes for delivering of MFA in vivo.